2019
DOI: 10.1021/acs.iecr.9b00670
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Impacts of Dissolved Organic Matter and Dissolved Iron on the Performance of Amidoxime-Based Adsorbents for Seawater Uranium Extraction

Abstract: One critical challenge of the development of seawater uranium extraction is to make uranium adsorbents perform well in the complex real seawater matrix, which is comprised of many competing ions and natural organic substances. Here, we conducted a systematic study using a continuous-flow seawater flume system to assess the potential impacts of dissolved organic matter (DOM) and dissolved iron on the uranium uptake performance, including adsorbent reusability, of amidoxime-based adsorbents. In the 28-day exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…[5a,27] In the presence of the HEIDI ligand at pH 3, U(VI) uptake decreases to 63.6 � 0.1 %. A decrease in the U(VI) loading in the presence of organic ligands (3.51 mg/L dissolved organic carbon) was also reported by Kuo et al, [8] where they observed a reduction of approximately 40 % compared to the U(VI) control at pH 7. In a separate study, Ahmad et al [28] reported a reduction of 11.1 % U(VI) in the presence of 25 mg/L of humic acid at pH 5.5.…”
Section: Uranium Adsorption Onto Ao-pan Matssupporting
confidence: 77%
See 3 more Smart Citations
“…[5a,27] In the presence of the HEIDI ligand at pH 3, U(VI) uptake decreases to 63.6 � 0.1 %. A decrease in the U(VI) loading in the presence of organic ligands (3.51 mg/L dissolved organic carbon) was also reported by Kuo et al, [8] where they observed a reduction of approximately 40 % compared to the U(VI) control at pH 7. In a separate study, Ahmad et al [28] reported a reduction of 11.1 % U(VI) in the presence of 25 mg/L of humic acid at pH 5.5.…”
Section: Uranium Adsorption Onto Ao-pan Matssupporting
confidence: 77%
“…However, there is no significant differences in the overall U(VI) uptake in any of these systems, which also indicates that these binary phases do not influence the ability of the AO‐PAN to effectively remove U(VI) from the system at a pH of 2–4. Under more alkaline conditions, Kuo et al [8] . did note that in the presence of Fe(III) the U(VI) capacity decreased to 43 % compared to the control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We employed a 63 L flume (length 1.22 m, width 0.20 m) and the target linear velocity was 2 cm/s in this study. The pH, salinity, temperature, trace elements, and dissolved organic carbon (DOC) of flume seawater were monitored throughout the experiment as described in previous literature [10,[14][15][16][17]. Three braided adsorbent materials were mounted in the circulating seawater flume system and flowed smoothly for 56 days at 20 • C. According to our published data [7,17], the uranium adsorption capacity of the amidoxime-carboxylate containing fiber reaches near equilibrium after 56 days of exposure to seawater.…”
Section: Methodsmentioning
confidence: 99%